Targeting Chemokine Receptor CXCR4 for Treatment of HIV-1 Infection, Tumor Progression, and Metastasis - Choi, Won-Tak (Curr Top Med Chem, 2014)
The chemokine receptor CXCR4 is required for the entry of human immunodeficiency virus type 1 (HIV-1) into target cells and for the development and dissemination of various types of cancers, including gastrointestinal, cutaneous, head and neck, pulmonary, gynecological, genitourinary, neurological, and hematological malignancies. The T-cell (T)-tropic HIV-1 strains use CXCR4 as the entry coreceptor; consequently, multiple CXCR4 antagonistic inhibitors have been developed for the treatment of acquired immune deficiency syndrome (AIDS). However, other potential applications of CXCR4 antagonists have become apparent since its discovery in 1996. In fact, increasing evidence demonstrates that epithelial and hematopoietic tumor cells exploit the interaction between CXCR4 and its natural ligand, stromal cell-derived factor (SDF)-1α, which normally regulates leukocyte migration. The CXCR4 and/or SDF-1α expression patterns in tumor cells also determine the sites of metastatic spread. In addition, the activation of CXCR4 by SDF-1α promotes invasion and proliferation of tumor cells, enhances tumor-associated neoangiogenesis, and assists in the degradation of the extracellular matrix and basement membrane. As such, the evaluation of CXCR4 and/or SDF-1α expression levels has a significant prognostic value in various types of malignancies. Several therapeutic challenges remain to be overcome before the use of CXCR4 inhibitors can be translated into clinical practice, but promising preclinical data demonstrate that CXCR4 antagonists can mobilize tumor cells from their protective microenvironments, interfere with their metastatic and tumorigenic potentials, and/or make tumor cells more susceptible to chemotherapy.